DESENVOLVIMENTO DE UMA BANCADA PARA TESTES DE VENTILADORES CENTRÍFUGOS - Basso, Samuel; Valdiero, Antonio C.; Bortolaia, Luiz A.; Santos, Felipe D.; Hoffmann, Roger S. (Salão do Conhecimento, 2013)
Resumo